FROM STORYTELLING TO STORY LIVING: EXPLORING THE METAVERSE AND ITS IMPLICATIONS FOR THE NEW AGE COMMUNICATOR - Dewan, Manas; Gagare, Ajit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the unfolding landscape of the Fifth Industrial Revolution, the concept of the "Metaverse" has found resonance within our collective consciousness. This paper presents a critical examination of the transformative potential of the Metaverse in the context of media and technology, emphasizing its implications for the field of communications. Rooted in a rhizomatic paradigm marked by continuous transformation, the Metaverse encapsulates augmented and virtual reality, blockchain, artificial Intelligence, and Web3.0 technologies. This study focuses on the Metaverse through the lens of the communicator, exploring immersive experiences powered by technological convergence and their potential impact on content. Building upon Baker et al.’s (2019) foundational insights, the research investigates the Metaverse’s influence on media engagement and societal shifts. Nicholson et al.’s (2014) findings on collaboration within virtual world technology and Petit et al.’s (2019) exploration of consumer acceptance of digital objects provide a nuanced understanding of immersive communication. In the post-pandemic era, marked by rapid digital acceleration, the paper evaluates the Metaverse’s role in shaping user behavior and societal structures, shedding light on its profound impact on media consumption patterns. Delving into the convergence of media and technology within the Metaverse, the paper explores its potential implications on immersive storytelling. It scrutinizes the evolving landscape where reification, presence, and immersion converge to give rise to the emergent scenario of "Story Living," blurring the boundaries between reality and simulation. The Metaverse prompts a deep and dynamic engagement with audiences and places them at the heart of the content piece. The introduction of interactivity and adaptive storytelling, facilitated by mixed reality technologies, empowers audiences to actively shape and participate in the narrative. This shift underscores the importance of adaptive multi-varied formats of communication within the immersive context of the Metaverse. Shin & Biocca’s (2017) research on virtual world, Chelsea et al.’s formulation of Hierarchy of Needs for User Experiences in Virtual Reality, as well as Thomas and David’s (1992) insights about modeling immersive environments provide a comprehensive analysis of the intersection between media, technology, and consumer experiences within this dynamic space. The paper seeks inspiration from Ahn et.al’s framework on bifold, triadic relationships to understand the nuances of human interactions unfolding in the metaverse. The paper acknowledges the adoption of the Metaverse beyond traditional gaming and corporate training. The integration of immersive environments by fashion brands, and investments by major brands in this space as outlined by Rauschnabel et al., (2022) signal an ongoing shift in brand focus. Shen’s (2002) examination of measurement methodologies and strategic considerations, underscores the need for critical assessment in academic discourse. By grasping the opportunities and challenges presented by the empowered audience within the Metaverse, this study enriches discussions on the cultural and societal impacts of the Metaverse for the new-age media communicator.